2016
DOI: 10.5812/cardiovascmed.31948
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of the right ventricular outflow tract palliation procedure in children with cyanotic congenital heart disease: A case-series study

Abstract: Background: The right ventricular outflow tract (RVOT) palliation has been shown to be a proper interventional procedure for lowering risk of mortality and improving clinical condition in cyanotic congenital heart disease (CHD) patients. Objectives: The present study aimed to assess the consequences of RVOT palliation in patients with TOF. Patients and Methods: This prospective case series was performed on 17 children who suffered from cyanotic CHD. The study endpoints were assessed by pulse oximetry, echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our findings are consistent with those of others studies that report remarkable growth of both PAs after either palliative approach (p < 0.05), which was valuable in high-risk cases, especially those with tet spells [3,5,8,17]. Despite the advantages of RVOT stenting over mBTS, early palliation in symptomatic infants increases the chance of requiring TAP at repair time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with those of others studies that report remarkable growth of both PAs after either palliative approach (p < 0.05), which was valuable in high-risk cases, especially those with tet spells [3,5,8,17]. Despite the advantages of RVOT stenting over mBTS, early palliation in symptomatic infants increases the chance of requiring TAP at repair time.…”
Section: Discussionsupporting
confidence: 92%
“…(MAPCA) are candidates for primary palliation as a first step to avert hypoxia, improvement of oxygen saturation and PAs development until the complete repair [2,7, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Mortezaeian et al showed the importance of repair surgery in improving oxygen saturation, low occurrence spell, and increased z-score of right and left pulmonary arteries (15). Therefore, they need PVR surgery at an older age compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricular outflow tract (RVOT) stenting is suggested as a promising yet underestimated alternative to aortopulmonary shunt in patients with low body weight. Furthermore, data on tissue response to RVOT stenting, particularly stent endothelialization in such patients are lacking …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, data on tissue response to RVOT stenting, particularly stent endothelialization in such patients are lacking. [9][10][11][12] Here, we evaluated clinical results of RVOT stenting in underweight, 1-to 3-month-old children with ToF and carried out a histological examination of the stented arterial segments upon TSG.…”
Section: Introductionmentioning
confidence: 99%